Incidence of congenital anomalies in Navodaya Medical College - D., Rita; Srividya, Baitinti; B. R., Geeta (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Congenital anomalies are defined as structural or functional anomalies including metabolic disorders, that occur during intrauterine life and can be identified antenatally, at birth or later in life. It accounts for 11% of neonatal deaths globally and accounts for 8–18% of perinatal deaths and 10–15% of neonatal deaths in India. Aims and objectives of the research were to study incidence and risk factors associated with congenital anomalies in Navodaya Medical College. Methods: The clinical study was done on 3008 patients over 1 year at Navodaya Medical College Hospital and Research Centre Thorough history, antenatal ultrasound, blood tests, new born babies were examined thoroughly by the paediatrician to detect the congenital malformation. If any internal congenital malformation were suspected further investigation like ultrasonography (USG), echocardiography (ECHO), X-ray, computed tomography (CT), and magnetic resonance imaging (MRI) were done. Results: Out of 3008 cases, 40 babies had congenital anomalies, incidence is 1.3%, most commonly involved system is musculoskeletal system followed by cardiovascular system. Major risk factors associated are extremes of age, parity, lack of ante natal check-ups, no intake of folic acid, maternal diabetes mellitus. Conclusions: Congenital malformations though cannot be prevented totally but can be minimised and if detected early which reduces mental agony in mother and family. Prenatal counselling, periconceptional folate, anomaly scan, prenatal diagnosis reduces the incidence of neonatal and infant morbidity and mortalities in India.